The Terrain of place-based education - Geoff Webber (Brock University, 2021)
The authors examine the terrain that has led to the creation of place based education in its current form. The history of PBE is developed through examination of the streams of influence: outdoor, experiential, environmental, critical educations, and Indigenous approaches. PBE is presented not as a re-packaging, nor a collection of, these progressive approaches. Rather, PBE is presented as an innovative nexus to address issues faced by educators in the 21st Century. The final stream affecting PBE is Indigenous approaches, or land based education which takes up Indigenous relationality. In the conclusion, the authors wonder if land based education is the heir to PBE, rather than an influence on it.